Pollen–pistil interaction in self-pollinated and sib pollinated flowers of sunnhemp (Crotalaria juncea L.) - P. Suriya1, N. Meenakshi ganesan1*, A. Subramanian1 and R. Gnanam2 (Electronic Journal of Plant Breeding, 2022)
Pollen pistil interaction studies were carried out in six sunnhemp genotypes. Pollen viability percentage of the six genotypes ranged from 0.0 to 93.5% and pollen germination ranged from 0.0 to 84.0% at four different floral stages starting from bud to opening of a flower. The viable pollen grains were present at the later three stages of flower for globose type anthers, while the pollen grains were viable at the later two floral stages for heart shaped anthers. Stigma receptivity was high to very high during S3 and S4 stages. Artificial self-pollination and sib pollination with a mixture of pollen grains were carried out and in vivo pollen tube growth in the style was investigated using fluorescence microscopy. In self-pollinated pistils, eight hours after pollination, callose wall development was seen around the nucellus cell. However, under sib pollinated pistil, eight hours after pollination, pollen tube penetrated into embryo sac of an ovule. The formation of callose in self-fertilized pistil prevented fertilization and seed set. But sib pollinated flowers were fertilized normally and a seed set could be observed. The investigation proved the existence of selfincompatibility.